Sudden suspected death in emergency department: Autopsy results - Gurger, Mehtap; Turkoglu, Abdurrahim; Atescelik, Metin; Bork, Turgay; Tokdemir, Mehmet; Alatas, Omer Dogan; Ekingen, Evren (Emergency Medicine Association of Turkey, 2014)
Objectives Sudden deaths occur within 24 hours after symptoms' onset and are caused by cardiac, neurological and pulmonary diseases. Autopsy is the gold standard in determining cause of death. In this study, death's etiology was evaluated in cases applied to our department that underwent autopsy with sudden death indication. Methods This study included cases aged 18 or older with sudden, suspected, non-traumatic death applying to our department between 2008 and 2012. Patients' age, sex, death time, co-morbid diseases, initial signs, cardiac rhythm, and autopsy findings were recorded after reviewing patient charts. Results The study included 46 patients. Mean age was 45.73±19.6. Of the cases, 84.78% applied to emergency with cardiopulmonary arrest. Thirty-two cases (69.6%) were male. The most frequent cause of death was cardiovascular diseases (52.2%), followed by central nervous system disorders (21.7%), intoxications (15.2%), and respiratory diseases (10.9%). The most common diseases were myocardial infarction (45.7%), subarachnoid hemorrhage (8.7%), and chronic obstructive pulmonary disease. There were three drug ingestions, three carbon monoxide intoxications, and one corrosive material ingestion among the intoxication cases. Conclusions Sudden deaths are rarely encountered. Emergency clinicians should consider cause in differential diagnosis and provide appropriate approaches at first evaluation.
Keywords: Autopsy; Emergency service; Sudden death